2017
DOI: 10.3390/ijerph14050548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drinking Water Disinfectant Byproducts Compliance Data as an Indirect Measure for Short-Term Exposure in Humans

Abstract: In the absence of shorter term disinfectant byproducts (DBPs) data on regulated Trihalomethanes (THMs) and Haloacetic acids (HAAs), epidemiologists and risk assessors have used long-term annual compliance (LRAA) or quarterly (QA) data to evaluate the association between DBP exposure and adverse birth outcomes, which resulted in inconclusive findings. Therefore, we evaluated the reliability of using long-term LRAA and QA data as an indirect measure for short-term exposure. Short-term residential tap water sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Site A contained higher amounts of chlorinated HAAs than Site B, which contained slightly higher levels of TOBr and brominated HAA species (e.g., BCAA). The difference in TOX and TOCl levels at the two sites is likely due to differences in amount of natural organic matter and water treatment conditions at the two sites, such as chlorine dose, reaction time, and residual time [6,28,34,54]. Contrary to TOX and TOCl, the measured levels of individual HAAs (except DCAA) in drinking water showed no significant site-specific differences.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Site A contained higher amounts of chlorinated HAAs than Site B, which contained slightly higher levels of TOBr and brominated HAA species (e.g., BCAA). The difference in TOX and TOCl levels at the two sites is likely due to differences in amount of natural organic matter and water treatment conditions at the two sites, such as chlorine dose, reaction time, and residual time [6,28,34,54]. Contrary to TOX and TOCl, the measured levels of individual HAAs (except DCAA) in drinking water showed no significant site-specific differences.…”
Section: Discussionmentioning
confidence: 95%
“…Most population-based epidemiologic studies use aggregated compliance data on five-HAAs for assessing their association with adverse reproductive outcomes. However, only a few studies reported the use of individual HAAs, especially urinary measures and reproductive health risk, which may provide more conclusive evidence of health risk [28]. For example, a retrospective cohort study from Central Arizona reported that the water concentrations of DCAA > 18 µg/L and TCAA > 17.8 µg/L increase the risk of small for gestational age (SGA), and the consumption of DBAA (>5 µg/L) and DCAA (>8 µg/L) later in pregnancy (weeks 33–40) elevate the risk of low birthweight and intrauterine growth restriction [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the temporal and spatial variability of DBPs throughout a distribution system [ 37 , 38 ], we cannot rule out that such sparse water sampling requirements contribute to exposure misclassification in our study. This is an important consideration due to the relatively short window of exposure relevant to birth defects and that LRAAs and quarterly averages can be problematic when used for brief exposure periods [ 39 ]. In addition to this Berkson-type measurement error, we must also consider that the DBP concentration estimates utilized in this study are susceptible to classical measurement error [ 40 ].…”
Section: Discussionmentioning
confidence: 99%